The Case of African International Students in China at the Height of COVID-19: International Higher Education’s Institutional Silence on Anti-Blackness - Agyenim-Boateng, Raymond; Watson, Ashley (Journal of International Students, 2023)
This scholarly reflection centers the experiences of African international students hosted in China during the height of the COVID-19 pandemic. Media coverage and photos of African student maltreatment during the first and second waves of COVID-19 are compiled after a cursory commentary of Sino-African relations. In the midst of soaring anti-Asian hatred around the world, African international students were discriminated against and subject to inhumane treatment across China. We acknowledge both of these violences coexist and call on critical interculturalist and agents of internationalization to consider issues of global anti-blackness and adopt an intersectional lens in studying international students’ experiences.